SOME THOUGHTS ON THE IMPORTANCE AND HISTORY OF THE LATIN LANGUAGE IN WORLD LANGUAGES - Sharipov Bobur Salimovich (Research Focus International Scientific Journal, 2023)
This article discusses the importance and history of the Latin language in today's world languages. It always shows the importance and weight of the Latin language in today's communication. In this regard, it is noteworthy that the terms of all fields, regardless of the language in which they are used, are not used in that language, but in Latin.